Influence of the ADP/ATP ratio, 2-oxoglutarate and divalent ions on Azospirillum brasilense PII protein signalling - Gerhardt, Edileusa C. M.; Araújo, Luíza M.; Ribeiro, Ronny R.; Chubatsu, Leda S.; Scarduelli, Marcelo; Rodrigues, Thiago E.; Monteiro, Rose A.; Pedrosa, Fábio O.; Souza, Emanuel M.; Huergo, Luciano F. (Microbiology (Society for General Microbiology), 2012)
Proteins belonging to the P(II) family coordinate cellular nitrogen metabolism by direct interaction with a variety of enzymes, transcriptional regulators and transporters. The sensing function of P(II) relies on its ability to bind the nitrogen/carbon signalling molecule 2-oxoglutarate (2-OG). In Proteobacteria, P(II) is further subject to reversible uridylylation according to the intracellular levels of glutamine, which reflect the cellular nitrogen status. A number of P(II) proteins have been shown to bind ADP and ATP in a competitive manner, suggesting that P(II) might act as an energy sensor. Here, we analyse the influence of the ADP/ATP ratio, 2-OG levels and divalent metal ions on in vitro uridylylation of the Azospirillum brasilense P(II) proteins GlnB and GlnZ, and on interaction with their targets AmtB, DraG and DraT. The results support the notion that the cellular concentration of 2-OG is a key factor governing occupation of the GlnB and GlnZ nucleotide binding sites by ATP or ADP, with high 2-OG levels favouring the occupation of P(II) by ATP. Both P(II) uridylylation and interaction with target proteins responded to the ADP/ATP ratio within the expected physiological range, supporting the concept that P(II) proteins might act as cellular energy sensors.